Poems $1 (BVolume 1s - Meredith, George, 1828-1909 (Salt Lake City, UT : Project Gutenberg, 1998)
"Poems $1 (BVolume 1" by George Meredith is a collection of poetry written during the late 19th century. This compilation showcases Meredith's mastery of various poetic forms and themes, reflecting on love, nature, and human experience, with demonstrated emotional depth and lyrical beauty. The opening of the collection begins with "Chillianwallah," which evokes the historical significance and somber aftermath of a battle, marked by lament and contemplation of loss. The poem sets a serious tone, blending personal grief with historical context. Following this, the fragment from "The Doe" presents a pastoral scene, highlighting the bond between a farmer$1 (Bs daughter and a captured fawn, interspersed with tender memories and nature's beauty. This excerpt illustrates Meredith's ability to weave intricate narratives that evoke vividly sentimental themes, suggesting a rich tapestry of reflections on life, love, and the interplay of humanity with nature throughout the collection. (This is an automatically generated summary.)s
Release date is 1998-07-01
Transcribed from the 1912 Times Book Club (3z(BSurrey Edition(3y (Bby David Prices
Keywords: English poetry; Pastoral poetry